An Analysis of Figurative Language on Online English Memes - Prasetiawan, Andika; Anindita, Widyashanti Kunthara (Applied Research on English Education (AREE), 2024)
The phenomenon of memes has been quite popular among internet users in recent years. Various types of memes have become a new culture for the audience on the internet. This research will analyze the figurative language that is often used by meme creators and the reasonS. This research is descriptive qualitative research. The data in this study are words, phrases, clauses, and sentences in Online English Memes. The sampling technique is purposive sampling technique. The data documentation technique is to search for Online English Memes on several provider sites on the internet (Reddit, 9GAG, Facebook). Data analysis techniques are data reduction, data display, and conclusion. The researcher used data triangulation to validate the data based on sources, methods, researcher, and theory. The research findings show figurative language that there were 23 data include words phrases, clauses, and sentences in 11 different types. The types with the highest number of occurrences are Alliteration, Hyperbole, Irony, and Metonymy, with 3 data. Meanwhile, the types with the lowest number of occurrences are Allusion, Metaphor, and Repetition, with 1 data. Personification, Sarcasm, Simile, and Symbol have 2 data. The reasons for using figurative language in memes are to create humour, to express emotions, to convey ideas, and to grab attention.